Complex transition metal hydrides incorporating ionic hydrogen: Synthesis and characterization of Na2Mg2FeH8 and Na2Mg2RuH8 - Humphries, Terry; Takagi, S.; Li, G.; Matsuo, M.; Sato, T.; Sørby, M.; Deledda, S.; Hauback, B.; Orimo, S. (Elsevier Ltd, 2015)
A new class of quaternary complex transition metal hydrides (Na2Mg2TH8 (T = Fe, Ru)) have been synthesized and their structures determined by combined synchrotron radiation X-ray and powder neutron diffraction. The compounds can be considered as a link between ionic and complex hydrides in terms of incorporating independently coordinated ionic and covalent hydrogen. These novel isostructural complex transition metal hydrides crystallize in the orthorhombic space group Pbam, where the octahedral complex hydride anion is surrounded by a cubic array of four Mg2+ and four Na+ cations, forming distinct two-dimensional layers. An intriguing feature of these materials is the distorted octahedral coordination of the isolated H− anions by four Na+ and two Mg2+ cations, which form layers between the transition metal containing layers. The vibrational modes of the H− anions and complex hydride anion are independently observed for the first time in a quaternary complex transition metal hydride system by Raman and IR spectroscopy.